Female calling, life cycle, and microstructures of the parasitic beetle Ripidius quadriceps Abeille de Perrin - Batelka, Jan; Straka, Jakub; Vávra, Jiří Ch; Škorpík, Martin; Prokop, Jakub (Journal of morphology, 2021)
The precopulatory behaviour of the larviform females of Ripidius quadriceps Abeille de Perrin, 1872 is described. The calling posture of virgin females is documented. The cephalic morphology and microstructures are visualised using scanning electron microscopy, in particular the secretory pores in the cuticle of inflatable maxillary palps. An exhaustive overview of relevant publications revealed that the location of secretory pores on the head of females is unique within the order Coleoptera. Compared to other beetles with sedentary calling females, the calling phase of the short-lived and non-feeding female of Ripidius is exceptionally short. For bioassays, various traps using virgin females of Ripidius were tested. It is likely that the sedentary behaviour of the short-lived female combined with a unique morphology and priority for investing in reproduction is compensated for by the actively flying males with remarkably flabellate antennae. The life cycle of this species, including some of the exceptions recorded at the individual level, is discussed. Perspectives for a biological and morphological survey of this rarely collected western Palaearctic species are outlined. In addition, the calling behaviour, secretory sites and location of pheromone glands in females of Coleoptera producing long range pheromones is reviewed.
Keywords: Animals; scanning electronic microscopy; rozmnožování; Female; Coleoptera; ženské pohlaví; Reproduction; Ripiphoridae; brouci; pheromone glands in females; stadia vývoje; hlava; Male; Vocalization, Animal; secretory pores and sensilla; Life Cycle Stages; zvířata; mužské pohlaví; Head; vokalizace zvířat